Japan's Policy Rationality in Cooperation with Myanmar Amidst Humanitarian Conflicts Post 2021-2023 - Fauzia Latifah Aini; Putri Mayang Rembulan; Ahmad Mujaddid Fachrurreza; Zahra Suci Ramadhani; Jesha Yemima Gunawan (Universitas Tribhuwana Tungga Dewi, 2025)
This study aims to elucidate the underlying factors driving Japan’s cooperation with Myanmar during the humanitarian crisis following the military coup. This study aims to uncover Japan’s unexpressed interests in maintaining its relationship with Myanmar, particularly as Japan becomes increasingly criticized. By applying rational choice theory, which is based on calculating the cost and benefit of each policy option, in addition to the logic of Neoclassical Realism to incorporate the interpretation of domestic institutions such as corporate interest and public opinion, it contains the rational choice dimensions of why Japan decided to adopt hedging strategy in Myanmar. The study employs a qualitative case study methodology incorporating process tracing to chart the evolution of Japan’s Southeast Asia policy through analysis of primary Ministry of Foreign Affairs documents, Official Development Assistance (ODA) data, and policymakers’ public speeches. The results provide evidence that Japan values long-term benefits in terms of resource access and strategic leverage to counterbalance China’s influence in Southeast Asia, while minimizing its reputational costs through limitations on direct assistance to the Tatmadaw. Moreover, the survey’s findings also suggest that, following the coup, boundedly rational decision-making under conditions of limited information led Japan not to impose humanitarian sanctions but to opt for a mixture of economic engagement and soft balancing. This research fills a gap in literature by demonstrating how state actors engage in rationalist calculations and thereby manage the tension between human values and national interests.Studi ini bertujuan untuk mengungkap minat Jepang yang tidak diungkapkan untuk menjaga hubungannya dengan Myanmar, khususnya, karena Jepang menjadi lebih dikritik. Dengan menerapkan teori pilihan rasional, yang didasarkan pada perhitungan biaya dan manfaat dalam setiap opsi kebijakan, selain logika Realisme Neoklasik untuk memasukkan interpretasi tentang institusi domestik seperti kepentingan perusahaan dan opini publik, ini mengandung dimensi pilihan rasional mengapa Jepang memutuskan untuk mengadopsi strategi lindung nilai di Myanmar. Pendekatan yang digunakan adalah studi kasus kualitatif dengan penelusuran proses yang digunakan untuk melacak perkembangan kebijakan Jepang yang ditujukan untuk Asia Timur dan Tenggara, dengan menganalisis dokumen kebijakan primer dari Kementerian Luar Negeri Jepang, data Bantuan Pembangunan Resmi (ODA), dan pidato publik yang dibuat oleh pembuat kebijakan. Hasilnya memberikan bukti bahwa Jepang menghargai manfaat jangka panjang dalam hal akses sumber daya dan pengaruh strategis untuk mengimbangi pengaruh Tiongkok di Asia Tenggara sambil meminimalkan biaya reputasinya melalui pembatasan bantuan langsung kepada Tatmadaw. Selain itu, temuan survei juga menunjukkan bahwa setelah kudeta, pengambilan keputusan yang sangat rasional dalam kondisi informasi terbatas membuat Jepang tidak menjatuhkan sanksi kemanusiaan, tetapi memilih campuran keterlibatan ekonomi dan penyeimbangan halus. Penelitian ini mengisi celah dalam literatur dengan menunjukkan bagaimana aktor negara terlibat dalam perhitungan rasionalis dan dengan demikian menangani ketegangan antara nilai-nilai kemanusiaan dan kepentingan nasional.